The Role of Ultrasonographic Monitoring for Hip Joint Changes in Patients with Chronic Renal Failure - Matoković, Damir; Hašpl, Miroslav; Petrić, Petar; Škorvaga, Sanja; Drkulec, Vlado; Šantak, Goran (IntechOpen, 2011)
None